Loss of Nuclear Functions of HOXA10 Is Associated With Testicular Cancer Proliferation - Chen, Ruiqi; Li, Haolong; Li, Yinan; Fazli, Ladan; Gleave, Martin; Nappi, Lucia; Dong, Xuesen (Frontiers in Oncology, 2018)
Background: HOXA10 is a key transcriptional factor that regulates testis development as seen from previous transgenic mouse models and human inherited diseases. However, whether it also plays important roles in promoting the development of testicular cancer is not well understood. Objective: To study the expression of HOXA10 and its regulated signaling pathways in testicular cancers. Design, Setting, and Participants: A tissue microarray was constructed with benign and cancerous testis. TCam2, NT-2, and NCCIT cell models were applied in this study. Intervention: Immunohistochemistry and immunofluorescence were performed to measure the expression and cellular localization of HOXA10 in testicular cancer tissues and cell models. Cell proliferation and cell cycling rates were determined by BrdU incorporation and flow cytometry assays. Ampliseq RNA-seq profiled HOXA10 transcriptome in testicular cancer cells. Immunoblotting assays were used to detect HOXA10-regulated signaling. Results: HOXA10 is a nuclear protein in benign spermatocytes. Reduced nuclear expression and increased cytoplasmic expression of HOXA10 are associated with testicular cancers. These changes are consistent in both seminoma and non-seminoma. Enhanced HOXA10 expression in testicular cancer cell models inhibits cell proliferation and delays cell cycle progression through G2/M phases. These HOXA10 functions mainly affect the TP53, Kit, STAT3, AKT and ERK signaling pathways. Conclusions: Loss of nuclear functions of HOXA10 enhances proliferation of testicular cancer cells, suggesting that downregulation of HOXA10 transcription activity may promote the development of testicular cancers.